Dynamics of motion of gases from a source of spontaneous combustion of coal in mine workings (Rudarsko-geološko-naftni zbornik, 2021)
The object of this paper is to study the specificity of the dynamics of carbon monoxide in mining to determine the location of the source of coal self-heating or spontaneous combustion. The Fire Dynamics Simulator software package was used to model the gas hazard of coal mine workings. Given the typical for the western coal basin of Donbas geometric dimensions of workings, properties of coal, etc., a model of a fragment of emergency mining of a coal mine was created, which allows to display geometric and physical similarity to processes in actual mine workings. The results of simulation for the studied scenarios with different air supply systems related to the detection and location of sources of self-heating or spontaneous combustion in the coal mine workings are obtained and analysed. It is established that low-density fire gases are concentrated in the vault of the workings, where they slowly dissolve in air, with the dissolution process being linear. It is revealed that air velocity up to 0.67 to 0.7 m/s contributes to formation of fire gas flows, which move towards the ventilation flow almost without mixing, which is referred to as bifurcation. Numerical parameters of fire gas dynamics in near-real conditions are established, which can become a basis for detection and location of sources of endogenous thermodynamic processes in mine workings.